Differential effect of vascularity between long‐ and short‐term survivors with IDH1/2 wild‐type glioblastoma. (19th January 2021) - Álvarez‐Torres, María del Mar; Fuster‐García, Elies; Reynés, Gaspar; Juan‐Albarracín, Javier; Chelebian, Eduard; Oleaga, Laura; Pineda, Jose; Auger, Cristina; Rovira, Alex; Emblem, Kyrre E.; Filice, Silvano; Mollà‐Olmos, Enrique; et al.
Abstract : Introduction: IDH1/2 wt glioblastoma (GB) represents the most lethal tumour of the central nervous system. Tumour vascularity is associated with overall survival (OS), and the clinical relevance of vascular markers, such as rCBV, has already been validated. Nevertheless, molecular and clinical factors may have different influences on the beneficial effect of a favourable vascular signature. Purpose: To evaluate the association between the rCBV and OS of IDH1/2 wt GB patients for long‐term survivors (LTSs) and short‐term survivors (STSs). Given that initial high rCBV may affect the patient's OS in follow‐up stages, we will assess whether a moderate vascularity is beneficial for OS in both groups of patients. Materials and methods: Ninety‐nine IDH1/2 wt GB patients were divided into LTSs (OS ≥ 400 days) and STSs (OS < 400 days). Mann‐Whitney and Fisher, uni‐ and multiparametric Cox, Aalen's additive regression and Kaplan‐Meier tests were carried out. Tumour vascularity was represented by the mean rCBV of the high angiogenic tumour (HAT) habitat computed through the haemodynamic tissue signature methodology (available on the ONCOhabitats platform). Results: For LTSs, we found a significant association between a moderate value of rCBVmean and higher OS (uni‐ and multiparametric Cox and Aalen's regression) ( p = 0.0140, HR = 1.19; p = 0.0085, HR = 1.22) and significant stratification capability ( p = 0.0343). For the STS group, no association between rCBVmean and survival was observed. Moreover, no significant differences ( p > 0.05) in gender, age, resection status, chemoradiation, or MGMT methylation were observed between LTSs and STSs. Conclusion: We have found different prognostic and stratification effects of the vascular marker for the LTS and STS groups. We propose the use of rCBVmean at HAT as a vascular marker clinically relevant for LTSs with IDH1/2 wt GB and maybe as a potential target for randomized clinical trials focused on this group of patients. Abstract : Long‐term survivors (>400 days) and short‐term survivors with IDH1/2 wild‐type glioblastoma are influenced differently by vascularity. Lower mean relative cerebral blood volumes (rCBVmean ) at high angiogenic tumour habitat are strongly associated with longer survival rates in long‐term survivors of IDH1/2 wild‐type glioblastoma. Factors such as MGMT methylation status and rCBVmean at high angiogenic tumour show a marked incremental effect on patient survival from 400 days from diagnosis, suggesting them as effective prognostic markers for the long‐term survivor group.